BRONCHOPROTECTIVE EFFECT OF GLYCOPYRRONIUM BROMIDE IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - I. N. Trofimenko; M. V. Genova; B. A. Chernyak (Медицинский совет, 2017)
Bronchial hyperreactivity (BHR) is one of the functional characteristics of chronic obstructive pulmonary disease (COPD) and is present in most patients with this disease. BHR has a negative modifying effect on the development of COPD, contributing to adverse prognosis and increased mortality compared to patients without bronchial hyperresponsiveness. The results of the evaluation of the impact of glycopyrronium bromide (GB) on BHR show a pronounced effect of the bronchoprotective broncholytic. The therapy by GB results in decrease in the level of BHR (p < 0.05), accompanied by a significant reduction of symptoms of COPD, improves tolerance to exercise and quality of life of patients in comparison with initial parameters (p < 0.05). Thus, BHR in patients with COPD appears to be an important criterion of therapeutic efficacy and decrease of the level of bronchial hyperresponsiveness has a significant clinical impact on the course of the disease.